2021
DOI: 10.1149/2162-8777/ac10b4
|View full text |Cite
|
Sign up to set email alerts
|

Promised Design of Energy-Efficient Negative-Capacitance Vertical Tunneling FET

Abstract: Ferroelectric materials are promising resources for boosting the performance of line or vertical tunneling-field transistors (VTFETs) by diminishing the voltage requirements. Here, we propose a promising VTFET design which has the benefits of HZO thin films having 50% of Zr composition on Hafnium oxide as Hf 0.5 Zr 0.5 O 2 . The significance of negative capacitance (NC) from Hf 0.5 Zr 0.5 O 2 on to VTFET is explored with the physical factors of the electric field and band-to-band tunneling. In addition, the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…It is to be understood that hysteresis-free operation can be achieved on several factors, such as by reducing the t fe and maintaining |C fe |C g (addressed in later sections). It is found that the t fe 5 nm is delivered with low hysteresis [43][44][45][46], the same can be perceived through our simulations as stated in figure 4(a) [22]. For controlled I off , the P r and E c are adjusted to 10 μC cm −2 and 1 MVcm −1 (as stated before).…”
Section: Significance Of Omfs-vtfetsupporting
confidence: 76%
See 1 more Smart Citation
“…It is to be understood that hysteresis-free operation can be achieved on several factors, such as by reducing the t fe and maintaining |C fe |C g (addressed in later sections). It is found that the t fe 5 nm is delivered with low hysteresis [43][44][45][46], the same can be perceived through our simulations as stated in figure 4(a) [22]. For controlled I off , the P r and E c are adjusted to 10 μC cm −2 and 1 MVcm −1 (as stated before).…”
Section: Significance Of Omfs-vtfetsupporting
confidence: 76%
“…Figure1. Simulations are endorsed with the measurement data for a ferroelectric TFET structure[7,22].…”
mentioning
confidence: 99%
“…Here, Q on and Q off represent the on-and off-charges of p-and n-CTFETs during on-and off-cycles. The factor of [32], ferroelectric utilization [28], low band bag semiconductors, and so on. As a future scope of CFET/CTFET, it is interesting to note the parasitic effect and their tradeoffs are challenging task in addition to FP H reduction (earlier stated).…”
Section: Ctfet-inverter Performancementioning
confidence: 99%
“…As a prior demonstration, CFET technology utilization for TFETs is restricted to conventional or point-tunneling rather advanced-tunneling approaches i. [28][29][30][31] In conclusion, the proposal for the design and exploration of CTFETs utilizing CFET technology for emerging technology nodes has been successfully delivered. The physical analyses and DC characteristic behavior have been discussed while highlighting the ability of CTFET under strict process conditions.…”
mentioning
confidence: 99%